E-004 Modeling the effect of hemodynamics on endothelial rna expression in cerebral aneurysms after endovascular flow diversion. (23rd July 2022) - Barros, G; Federico, E; Fillingham, P; Xue, J; Kaneko, N; Zheng, Y; Levitt, M
Abstract : Introduction: Flow diverting stents (FDS) are a valuable endovascular option to treat unruptured cerebral aneurysms, with a single endoluminal device in the parent vessel ultimately promoting thrombosis and occlusion of the aneurysm sac. Flow diversion has yielded promising long-term aneurysm occlusion data; however, retreatment is required in up to 8% by 2 years. Questions remain about the biologic responses behind treatment successes and failures. The goal of this study is to understand how changes in hemodynamic flow after FDS placement affect aneurysmal endothelial RNA expression associated with treatment success or failure. Methods: An in vitro, patient-specific three-dimensional aneurysm model with pre- and post-FDS treatment conditions was created to quantify the endothelial response specific to hemodynamic changes within the aneurysm dome seen on computational flow dynamic (CFD) simulations. Each model was seeded with human carotid endothelial cells and then subjected to pulsatile flow with patient-specific mean blood flow velocity for 24 hours ( Figure 1 ). RNA was isolated from aneurysm dome, along with proximal and distal parent vessels serving as internal controls for each patient. The same experiments are performed both before and after FDS placement using commercially available FDS (Pipeline Embolization Device). Results: Six unique patients with intracranial internal carotid artery aneurysms treated with FDS were included, of which three had successful treatments with complete occlusion, while three had treatment failure with persistent aneurysm filling requiring retreatment. Experiments are currently ongoing, with four of six pre-treatment models completed endothelial cell seeding, exposure to flow, and RNA isolation. Post-treatment models with implanted FDS will then undergo the same experiment. We then will use the colocalized CFD and RNA expression data to identify patterns consistent with treatment outcomes. Bulk RNA sequencing will be completed on each sample. Conclusions: Direct study of the vascular endothelial response to changes in hemodynamic stress experienced in cerebral aneurysms after FDS has not yet been performed. This study could address the knowledge gap regarding the mechanisms of treatment outcome and angiographic occlusion, to ultimately improve endovascular treatments of cerebral aneurysms. Disclosures: G. Barros: None. E. Federico: None. P. Fillingham: None. J. Xue: None. N. Kaneko: None. Y. Zheng: None. M. Levitt: 1; C; Stryker, Medtronic. 2; C; Medtronic, Metis Innovative. 4; C; Synchron, Cerebrotech, Proprio, Hyperion Surgical.